2020
DOI: 10.1177/1534734620948343
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ultrasound Therapy in the Management of Musculoskeletal Soft Tissue Pain

Abstract: Ultrasound is an invaluable physical modality widely used for diagnosis and therapy in humans and animals. It is noninvasive, atraumatic, and may be used repeatedly. As a therapeutic tool, ultrasound has been in use for some 6 decades. Therapeutic ultrasound (TUS) is used for the treatment of musculoskeletal disorders, including acute soft tissue injuries, overuse syndromes, as well as chronic orthopedic and rheumatologic conditions. The aim of this review was to investigate the clinical effectiveness of TUS i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 57 publications
0
16
0
2
Order By: Relevance
“…And it also encouraged tendonbone junction healing by enhancing tissue performance. [14] Therapist had given carpometacarpal glide which was supported by Karen Maloney Backstrom study in the year 2002 that is Mobilization with movement as an adjunct intervention in a patient with complicated de Quervain's tenosynovitis which demonstrated that an efficient and successful physical therapy method was involving Movement With Mobilization with active mobility of the wrist and 1st carpometacarpal joint. A promising improvement was noted in the range of motion and pain on Numeric pain rating scale {TABLE 1 AND 2}.…”
Section: Discussionmentioning
confidence: 97%
“…And it also encouraged tendonbone junction healing by enhancing tissue performance. [14] Therapist had given carpometacarpal glide which was supported by Karen Maloney Backstrom study in the year 2002 that is Mobilization with movement as an adjunct intervention in a patient with complicated de Quervain's tenosynovitis which demonstrated that an efficient and successful physical therapy method was involving Movement With Mobilization with active mobility of the wrist and 1st carpometacarpal joint. A promising improvement was noted in the range of motion and pain on Numeric pain rating scale {TABLE 1 AND 2}.…”
Section: Discussionmentioning
confidence: 97%
“…Our ndings are consistent with previous studies that demonstrated low-intensity ultrasound's effectiveness in lowering patients' pain following acute soft tissue injury. [18] , [19] , [20] Victoria [21] and Andrew [22] discovered that ultrasound therapy for patients with Achilles tendon illness dramatically decreased pain compared to pre-treatment levels. And in a different study, the VAS pain score started to decline only in the second week compared to baseline in patients with lateral epicondylitis disease after 8 weeks of LIPUS treatment at a frequency of 1 MHz and an intensity of 1 W/cm2.…”
Section: Discussionmentioning
confidence: 99%
“…The US beam produces longitudinal waves that cause thermal changes in the tissue. Thermal effects on the US include: increased tissue temperature, increased local blood flow, and increased extensibility of collagen fibers (Papadopoulos & Mani, 2020). Joint mobilization positively influences neuroimmune responses in neuromusculoskeletal conditions (Lutke Schipholt et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Thermal effects of UST include: increased tissue temperature, increased local blood flow, and beneficial for increasing the extensibility of collagen fibers which have an impact on reducing pain and increasing flexibility in NSLBP patients (Papadopoulos & Mani, 2020).…”
Section: Introductionmentioning
confidence: 99%